2014
DOI: 10.1631/jzus.b1300171
|View full text |Cite
|
Sign up to set email alerts
|

Expression of three essential antioxidants of Helicobacter pylori in clinical isolates

Abstract: Abstract:Objective: Helicobacter pylori maintains long-term persistence in the host and combats oxidative stress via many antioxidant proteins, which are expected to be relevant to bacterial-associated gastric diseases. We aimed to investigate the expression of three essential antioxidants in H. pylori strains isolated from patients with different clinical outcomes. Methods: Forty H. pylori strains were isolated from endoscopic biopsy specimens of gastric mucosa from 13 patients with gastric cancer, 13 with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Previously our data also revealed another two anti-oxidative factors, the arginase (RocF) and alkyl-hydroperoxide reductase (AhpC) levels were also higher in H. pylori isolated from gastric cancer patients [17]. RocF is also an important part of H. pylori redox system as Trx-1.…”
Section: Relationship Between Trx-1 and Other Antioxidant Memberssupporting
confidence: 54%
See 1 more Smart Citation
“…Previously our data also revealed another two anti-oxidative factors, the arginase (RocF) and alkyl-hydroperoxide reductase (AhpC) levels were also higher in H. pylori isolated from gastric cancer patients [17]. RocF is also an important part of H. pylori redox system as Trx-1.…”
Section: Relationship Between Trx-1 and Other Antioxidant Memberssupporting
confidence: 54%
“…The RocF level was also higher in H. pylori isolated from cancer patients. What's more, our data showed a positive correlation trend between Trx-1 and AphC, although there was no linear trend, it might due to the limited sample number [17]. So we might come to the conclusion that it is the antioxidant enzyme system including Trx-1, RocF and AphC that contribute to the long term colonization of H. pylori in host stomach, and avoid H. pylori from oxidative damage.…”
Section: Relationship Between Trx-1 and Other Antioxidant Membersmentioning
confidence: 59%
“…DNA damage can be detected in the gastric mucosa during HP infection [ 17 , 28 ]. Our previous study found that the high-Trx1 HP was related to stronger cellular stress and redox activity-related proteins [ 29 , 30 ]. Consistent with the previous studies, we found that HP with high expression of Trx1 can produce much more 8-OHDG, suggesting that 8-OHDG may be one of the pathogenic mechanisms of HP Trx1.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some authors associate the presence of arginases, especially ARG2 , with the escape mechanisms of H. pylori , by causing a low availability of L-arginine and thus inhibiting the NOS2-dependent microbicidal activity. Moreover, the expression of arginase by H. pylori itself was associated with its carcinogenic activity [26]. We believe that the patients with chronic inactive gastritis established a mechanism of protection against infection, and with an increase in ARG1 , established a modulation process for regeneration.…”
Section: Discussionmentioning
confidence: 99%